Cities between Competitiveness and Cohesion
XVIII, 306 p.
Keywords: The book is the result of a COST Action financed by the European Science Foundation. It analyses the key concepts, ideas and processes driving competitiveness and cohesion agendas across Europe and demonstrates the implications and the effects of contemporary urban regeneration policies and politics in Europe. The case study material ensures that an in depth understanding of policy processes is conveyed to readers, and attention is drawn to the problems and paradoxes of policy, but also to the possibilities for policy innovation and learning across national and disciplinary borders. The material a.o. studies the cities of Amsterdam, Antwerp, Athens, Bratislava, Istanbul, Maribor, London, Rotterdam, Vienna, and Zurich. Specific policy fields which are looked at relate to housing, labour markets, enterprises, integration of ethnical groups, urban regeneration, or transport. The book shows that spatial and urban policy continues to be a key site of policy intervention and experimentation. Different national welfare systems, political cultures, and socio-economic conditions combine and recombine to address policy problems and opportunities. Collectively, the authors argue that the examined policy initiatives reflect and reproduce these broader changes and shifting ways of thinking about the appropriate relationships between citizens, businesses, and the state.